Scientific tafsôr: motive, development and disputes over its permissibility - Rahman, Mizanur; Osmani, Noor Mohammad (Pusat Tamhidi, Universiti Sains Islam Malaysia, 2016)
There are several established approaches to TafsÊr- interpretation of the holy Qur´Én. Al- TafsÊr al-‘IlmÊ - the scientific interpretation of the Holy Qur´Én is one of the approaches which is lately emerged in the discipline of TafsÊr. There are disputes among the scholars over the permissibility of scientific interpretation of the Holy Qur´Én. Some of them are in favor of this approach while others regard it impermissible and interpret the Qur´Énic verses only from the linguistic angle. Since the Holy Qur´Én- the ultimate Book of Guidance covers all aspects of human life, it addresses natural sciences in various places. Moreover, almost one eighth of the total number of verses of the Qur´Én is devoted to several natural phenomena. In this connection, this paper aims to clarify the issue of scientific interpretation all about with a special focus of scholar’s viewpoints on its legitimacy using an analytical method. The most significant finding of this paper is that scientific interpretation is permissible with some conditions. This paper also concluded that without having proper Qur´Énic knowledge and scientific insights, no one should talk about the natural phenomena and the scientific indications mentioned in the Holy Qur´Én; otherwise, it may lead to misinterpretation of the holy book of Allah, revealed for the guidance of humankind.